Influential Factors in Project Knowledge Management of Public Library Projects Using the System Dynamics Approach - Sara Najari; Amir Rezaee (نشریه مطالعات دانش‌پژوهی, 2024)
Purpose: This study aims to identify the factors influencing the knowledge management of public library projects in Iran.Methodology: The system dynamics method was employed, which is descriptive and practical in nature. The statistical population consisted of 10 project knowledge specialists and experts in Iran, selected using the snowball method.Findings: Cause and effect loops were established, considering modes of learning before, during, and after the project, as well as learning from external sources. The parameters were determined through interviews with project knowledge management specialists. The findings indicated that a ten percent increase in system integrity over five years led to a 1.4 percent increase in project knowledge. Scenario building was conducted based on these results.Conclusion: To enhance the knowledge management system of public library projects, it is essential to plan for effective knowledge transfer before, during, and after the project, integrate systems, measure performance, extract new knowledge, and utilize external resources, as well as establish organizational networks.Value: This research fills a gap in the literature by examining the factors influencing project knowledge management using the system dynamics approach. It has the potential to enhance organizational performance and serve as a basis for future research.